Ultrafine Bimetallic Pt–Ni Nanoparticles Achieved by Metal–Organic Framework Templated Zirconia/Porous Carbon/Reduced Graphene Oxide: Remarkable Catalytic Activity in Dehydrogenation of Hydrous Hydrazine. Issue 1 (18th November 2019) - Song, Fu‐Zhan; Yang, Xinchun; Xu, Qiang
Abstract: Emerging as a promising hydrogen carrier, hydrous hydrazine has attracted great attention in hydrogen storage and transportation. Herein, by using a wet‐chemical reduction method, ultrafine bimetallic PtNi nanoparticles (NPs) with an average size of 1.8 nm are immobilized on a metal–organic framework templated zirconia/porous carbon/reduced graphene oxide (ZrO2 /C/rGO) support. Monometallic Pt and Ni NPs show no activities for the catalytic dehydrogenation of hydrous hydrazine. Surprisingly, the obtained bimetallic Pt–Ni NPs exhibits a significantly enhanced catalytic activity toward the hydrogen generation from hydrous hydrazine, with which an extremely high turnover frequency value can be afforded to 1920 h −1 at 323 K. The highly enhanced catalytic activity can be attributed to the small size effect, the strong synergistic effect between Pt and Ni atoms as well as the strong metal‐support interactions. The present work provides a new insight to developing high‐performance bimetallic catalysts for advanced catalytic and energy technologies. Abstract : Ultrafine and highly dispersed bimetallic PtNi nanoparticles (NPs) are immobilized on a metal–organic framework templated zirconia/porous carbon/reduced graphene oxide by a facile wet‐chemical reduction method, which exhibit significantly high catalytic activity toward the hydrogen evolution from hydrous hydrazine.